2024
DOI: 10.3390/land13010064
|View full text |Cite
|
Sign up to set email alerts
|

Rice Terrace Experience in Japan: An Ode to the Beauty of Seasonality and Nostalgia

Qian Wang,
Xiaoqi Yang,
Xinyu Liu
et al.

Abstract: Rice terraces are a time-honored agricultural feature that overcomes rough terrain and hostile growing conditions. In addition to playing an essential role in agricultural production and land conservation, rice terraces have been recognized as living cultural landscapes, important agricultural heritage, and popular agritourism destinations for their aesthetic, sociocultural, and environmental values. However, there is a lack of understanding of this emerging niche market, especially from outsider perspectives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…In addition, seasonal change is probably cause differences in people's perception of the landscape environment. For example, a study of seasonal rice terrace landscapes in Japan showed that tourists had a higher overall positive experience in summer than in autumn, which was related to the barrenness of farmland in autumn [38]. Another study of landscape features affecting visitor density in integrated parks showed that zones with a higher shading degree attracted more visitors in summer and deterred visitors in winter [39].…”
Section: Factors Affecting Landscape Perception and Preferencementioning
confidence: 99%
“…In addition, seasonal change is probably cause differences in people's perception of the landscape environment. For example, a study of seasonal rice terrace landscapes in Japan showed that tourists had a higher overall positive experience in summer than in autumn, which was related to the barrenness of farmland in autumn [38]. Another study of landscape features affecting visitor density in integrated parks showed that zones with a higher shading degree attracted more visitors in summer and deterred visitors in winter [39].…”
Section: Factors Affecting Landscape Perception and Preferencementioning
confidence: 99%